New Dynamic Model for Servo Motors. Simulations and Experimental Results - Urrea-Onate, E; Kern-Molina, J (IEEE Computer Society, 2014)
In this paper a new dynamic model for analogic servomotors is proposed. Then, an analytical model is initially developed, after which, through computer simulations the obtained theoretical results are validated. Those results are contrasted, with practical implementations, by employing a real analog servo motor. This new model can capture the dynamics resulting from the servomotor axis of rotation by including the internal position feedback; as well as considering the increased torque on the axle load, reached by means of their gear train. The development of this new proposed model permits the recovery of relevant properties of the servo motors. This will allow the study and develop more advanced control techniques, compared to those currently can be used by employing a classic DC motor model. © 2003-2012 IEEE.